E3 Ubiquitin Ligase OsRFI2 Regulates Salinity Tolerance by Targeting Ascorbate Peroxidase OsAPX8 for its Degradation in Rice - Wenjing Zhao; Junli Wen; Juan Zhao; Linlin Liu; Mei Wang; Menghan Huang; Chaowei Fang; Qingpo Liu (Rice)
Abstract Salinity is a major abiotic stress that adversely affects rice growth and production. However, the detailed regulatory mechanisms of salt stress response in rice remain largely unexplored. In this study, we established that the RING-type E3 ubiquitin ligase OsRFI2 plays a negative role in salt tolerance in rice. Knockout mutants of OsRFI2 (Osrfi2) exhibited high tolerance, whereas OsRFI2-overexpressed transgenic lines (OE-OsRFI2) were more sensitive to salt stress. OsRFI2 that has E3 ligase activity interacts with ascorbate peroxidase OsAPX8 in chloroplast, and catalyzes its ubiquitination and degradation through the 26 S proteasome pathway. The Osapx8 mutants, like OE-OsRFI2 lines, showed high sensitivity to high salt concentrations, accumulating greater amounts of MDA, H2O2 and O2 −, which lead to compromised cell permeability and ROS accumulation. Thus, the OsRFI2-OsAPX8 module adds novel clues for better understanding the regulatory mechanism of salt stress response in rice.